2015
DOI: 10.1111/jfpe.12322
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Bioactive Capacity of Mixed Juice Scum Extracts from Sugarcane Mills

Abstract: The scum is a semisolid by-product in canesugar mills where flotation technology is used for mixed juice clarification. To evaluate its potential bioactive properties, an aqueous extract, a 70% ethanol extract and a 100% ethanol extract from the scum were obtained and used for antioxidant activity assessment. Chemical assays of 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2 0 -azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) diammonium salt (ABTS) were used to determine the total antioxidant activity, and a chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…(c) Variations in different products of sugarcane processing (brown sugar [ 10 , 59 , 60 ], white sugar [ 8 , 59 , 60 ], refined sugar [ 59 ], and non-centrifugal sugar (NCS) [ 59 , 60 ]). (d) Variations in different by-products generated during sugarcane processing (bagasse [ 42 , 43 ], scum [ 47 ], filter mud [ 45 ], molasses [ 8 , 45 , 65 , 108 ], and vinasse [ 9 ]). NR: Data not reported.…”
Section: Bioactive Compounds From Sugarcane and Its Derivativesmentioning
confidence: 99%
See 3 more Smart Citations
“…(c) Variations in different products of sugarcane processing (brown sugar [ 10 , 59 , 60 ], white sugar [ 8 , 59 , 60 ], refined sugar [ 59 ], and non-centrifugal sugar (NCS) [ 59 , 60 ]). (d) Variations in different by-products generated during sugarcane processing (bagasse [ 42 , 43 ], scum [ 47 ], filter mud [ 45 ], molasses [ 8 , 45 , 65 , 108 ], and vinasse [ 9 ]). NR: Data not reported.…”
Section: Bioactive Compounds From Sugarcane and Its Derivativesmentioning
confidence: 99%
“…This suspended material, called scum, is removed by filtration to obtain an insoluble-solids-free juice known as draft juice [ 45 , 46 ]. Some studies have reported that scum can be considered as a suitable by-product for extracting BCs, since contents of around 25.8 mg of polyphenols/g of sample (on a dry matter basis) have been reported, and it presents a high association with antioxidant activities in vitro [ 47 , 48 ]. Concerning the raw juice, this is a turbid liquid with a marked coloration in different green-brown shades and serves as a substrate for the subsequent extraction of sucrose.…”
Section: Bioactive Compounds From Sugarcane and Its Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…The enrichment of these hydrophobic substances at the gas-liquid interface of the bubbles leads to the formation of a foam layer, which is rich in the desired compounds and is collected readily (Ma, Xiu et al 2002). Compared to conventional separations, bubble separation holds certain advantages (Lu, Pu et al 2017). The adsorption process is less favorable for compounds with a high molecular weight, which would reduce the amount of fat and chlorophyll contaminating the extract.…”
Section: Introductionmentioning
confidence: 99%